Taktik Utama Kepribadian Covert Aggressive pada Tokoh Prospera Mercury (プロスペラ・マーキュリー) dalam Anime Kidou Senshi Gundam: Suisei no Majo - Jauhari, Tantowi; Andari, Novi (Vocational College of Diponegoro University, 2024)
Aggressiveness is a human behavior necessary for achieving life goals, characterized by both positive and negative traits. One form of negative aggressiveness is covert aggressive. Individuals with a covert aggressive personality tend to be dominant and manipulative. Literature reflects life, as seen in the anime